Engaging stakeholders in pharmacoepidemiology research: Current state and recommendations. Issue 6 (2nd May 2019) - Camelo Castillo, Wendy; Heath, Nicholas; Kim, John; Yang, Kimberly; Ritchey, Mary E.; dosReis, Susan; Santanello, Nancy; West, Suzanne L.
Abstract: Purpose: Given current efforts to enhance patient‐centered care and shared decision‐making, the International Society of Pharmacoepidemiology Workgroup on Patient Engagement assessed patient and other stakeholder engagement in pharmacoepidemiology research and provides recommendations for the field. Methods: A systematic review used MEDLINE and EMBASE to identify published literature from 2005 to 2016 addressing how stakeholders—patients, caregivers, and others—assisted researchers conducting pharmacoepidemiologic research. Three pairs of Workgroup members screened titles and abstracts to select articles for full‐text review and analysis. Two Workgroup members abstracted the following data: research focus, characterization and role of stakeholders, and type(s) of engagement strategy employed. Data were summarized descriptively. Results: We identified 5717 references for abstract screening. Of these, 69 met the criteria for full‐text screening, and 11 were selected for data abstraction. Of these 11 studies, seven focused on the development of a research agenda and eight had stakeholders react or advise on an aspect of the study. Although patients were the most commonly identified stakeholders, advocacy groups and health care professionals were also frequently identified. Some studies reported the engagement of other stakeholders, including local government or policy experts. Engagement strategies varied, with five studies using more than one strategy. Studies often did not indicate the involvement of stakeholders in developing the study design or with implementation. Conclusions: Currently, few pharmacoepidemiology publications mention patient or other stakeholder engagement in the design, analysis, or reporting of research. This suggests that there are opportunities to expand stakeholder engagement and/or increase the transparency of reporting stakeholder engagement.